Coping And Mental Health - Bourouba Hana; Louchahi Farida (University of Eloued جامعة الوادي, 2023)
In this study, we will address the role of coping strategies to psychological stress in maintaining the mantel health of the individual in a theoretical and analytically form, where we discussed the concepts of both terms with an emphasis on the coping functions of strategies that highlight their role in maintaining mental health or attempting to mitigate risk factors. Leading to the explosion of psychological and psychosomatic disorders of progressive severity and restoring the inner balance and adjustment of the stressed person based on the Lazarus and Folkman model, which identifies two types of strategies for coping with stressful situations. The analysis of this role was made by linking the first concept to the analysis of the basic manifestations of mental health, that is to say that the maintenance of the manifestations of mental health is the first objective of the use of an individual in case he is faced with a specific problem that threatens his internal balance to an adaptive strategy or strategies that preserve for him the psychological, physical and social entity.
analytical Theory Study
Keywords: coping; mental health; strategy; confrontation